Review of recent advances in research on the toxicity, detection, occurrence and fate of cyclic volatile methyl siloxanes in the environment - Wang, De-Gao; Norwood, Warren; Alaee, Mehran; Byer, Jonathan D.; Brimble, Samantha (Chemosphere (Oxford), 2013)
► A critical assessment of the current state of knowledge of toxicity, fate, and environmental levels of cVMS is presented. ► An overview of the use, physico-chemical properties, methods of detection, of the three most widely used cVMS is reported. ► Knowledge gaps and recommendations for future research on cVMS have been identified. The fate and behavior of cyclic volatile methylsiloxanes (cVMS) octamethylcyclotetrasiloxane (D4), decamethylcyclopentasiloxane (D5), and dodecamethylcyclohexasiloxane (D6) in the environment were reviewed. We evaluated their usage data and patterns, physico-chemical properties, toxicology, partitioning and degradation, methods of detection, and concentrations. The use of cVMS as an intermediate in the formation of silicone polymers, personal care and household products has resulted in their widespread environmental exposure; they have been detected in biogas, air, water, soil, biosolid, sediment, and biota samples. Modeled and experimental results suggest that cVMS may be subject to long-range atmospheric transport, but have low potential to contaminate the Arctic. For D4 and D5, there was no evidence of trophic biomagnification in aquatic food webs, while some aquatic organisms demonstrated a high degree of bioconcentration and bioaccumulation. High concentrations of cVMS observed in indoor air and biosolids resulted from point sources. Concentrations of cVMS in water, sediment, and soil were all below their no-observed-effect-concentrations.